Elizabeth Bishop and the Literary Archive - Hicok, Bethany (Lever Press, 2020)
In a life full of chaos and travel, Elizabeth Bishop managed to preserve and even partially catalog, a large collection-more than 3,500 pages of drafts of poems and prose, notebooks, memorabilia, artwork, hundreds of letters to major poets and writers, and thousands of books-now housed at Vassar College. Informed by archival theory and practice, as well as a deep appreciation of Bishop's poetics, the collection charts new territory for teaching and reading American poetry at the intersection of the institutional archive, literary study, the liberal arts college, and the digital humanities. The fifteen essays in this collection use this archive as a subject, and, for the first time, argue for the critical importance of working with and describing original documents in order to understand the relationship between this most archival of poets and her own archive. This collection features a unique set of interdisciplinary scholars, archivists, translators, and poets, who approach the archive collaboratively and from multiple perspectives. The contributions explore remarkable new acquisitions, such as Bishop's letters to her psychoanalyst, one of the most detailed psychosexual memoirs of any twentieth century poet and the exuberant correspondence with her final partner, Alice Methfessel, an important series of queer love letters of the 20th century. Lever Press's digital environment allows the contributors to present some of the visual experience of the archive, such as Bishop's extraordinary "multi-medial" and "multimodal" notebooks, in order to reveal aspects of the poet's complex composition process.